Do CE mandates impact the number of CE providers and licensing board complaints? A longitudinal look. Issue 7 (3rd October 2021) - Rothke, Steven E.; Neimeyer, Greg J.; Taylor, Jennifer M.; Zemansky, Mary F.
ABSTRACT: With few exceptions, the effectiveness of continuing education (CE) mandates has been measured by self-report assessments of the professional psychologists who fulfill them. The present investigation provided a longitudinal look at the number of approved CE providers and the incidence of licensing board complaints across a succession of two-year cycles prior to, and following, the 2012 implementation of CE mandates in the State of Illinois. Findings showed a substantial increase in the number of CE providers across that time, though no significant change in the incidence of licensing board complaints, suggesting that the increased availability of CE did not translate into lower complaint rates. Possible reasons for these findings are noted, and recommendations for future work are detailed in support of an evidence-based approach to CE that better articulates and aligns its objectives with its outcomes in an era of renewed accountability in the health professions.